The Cholevinae of Romania (exclusive of Leptodirini) (Coleoptera, Leiodidae) with special reference to the hypogeal records - Nitzu, Eugen (Zootaxa, 2013)
The first catalogue of the Romanian Cholevinae (excluding Leptodirini) is presented, based on revised and new records. The overall distribution and distribution in Romania are documented for every species, with particular reference to subterranean environment (caves and subterranean superficial environment). Epigeal and hypogeal records are listed separately. Thirty two of forty nine species group taxa recorded in the Romanian fauna occur both in the epigeal and subterranean environment, 14 of them frequently recorded in the latter. Many species, dependant on the subterranean environment during certain stages of their life cycle, are considered troglophilic or subtroglophilic: Choleva cisteloides dacica Jeannel 1922, Ch. glauca Britten, 1918, Catops picipes Fabricius, 1792, C. longulus Kellner, 1846 and C. tristis Panzer, 1874. The Romanian fauna of Cholevinae is more similar to that of the Central Europe than the Balkan Peninsula.